Optimization of COD removal from leachate nanofiltration concentrate using H2O2/Fe+2/heat - Activated persulfate oxidation processes - Guvenc, Senem Yazici (ELSEVIER, 2019)
This study aimed to remove COD from leachate nanofiltration concentrate (LNFC) by oxidation of H2O2/Fe2+/Heat - activated persulfate (PS) and optimization and modelling of its removal using a Central Composite Design (CCD) by the Response Surface Methodology (RSM). In the results of ANOVA where the experimental data of the study were analyzed, high correlation coefficients (R-2 > 0.80) were obtained from all three processes, and it was seen that models could be explained by these data. The COD removal efficiencies under the optimum conditions for the H2O2, Fe2+ and Heat - activated PS processes were 56.9%, 76.2% and 93.5%, respectively. About 64.3%, 78% and 93.2% removal efficiency values of inert COD were obtained after the H2O2-activated PS, Fe2+-activated PS and Heat-activated PS processes, respectively. Consequently, the heat-activated PS process may be an alternative technology for COD and inert COD removal from leachate nanofiltration concentrate. (C) 2019 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Leachate nanofiltration concentrate; Persulfate oxidation; Response surface methodology; COD fractions; STABILIZED LANDFILL LEACHATE; DISSOLVED ORGANIC-MATTER; WASTE-WATER TREATMENT; FENTON OXIDATION; NITROGEN REMOVAL; AQUEOUS-SOLUTION; DEGRADATION; HEAT; OZONE/PERSULFATE; PRETREATMENT; Engineering